Model Antrian Multi Channel Single Phase Berdasarkan Pola Kedatangan Pasien untuk Pengambilan Obat di Apotik - Yuliana, Devi; Santony, Julius; Sumijan (Jurnal Informasi dan Teknologi, 2019)
The accumulation of queues of prospective patients also results in an inadequate waiting room, which occurs because there is no disciplinary pathway that can provide a form of registration service that is efficient and flexible with time to many entry points and many services so that patients do not have to queue long only to take medicine. The solution to handling the problem of the accumulation of prospective patients in RSI Ibnu Sina Padang is to implement a multi-channel queuing system - Single phase, where there will be more than one entry point to register to RSI Ibnu Sina Padang so that the patient arrival pattern is divided into several times and the path is adjusted with the needs of the patient's desired time and there is more than one stage of service at Ibnu Sina Hospital in Padang. The purpose of this study was to design a php application at the Ibnu Sina Hospital in Padang with the Multi Single Phase Method and find out the time spent by patients in the queue, then it is expected to be useful for the RSI Ibu Sina Padang.